2010
DOI: 10.1007/s12237-010-9304-3
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent Stable Isotope Analysis of Consumers in the Upper Reaches of a Freshwater-dominated Estuary: Apalachicola Bay, FL, USA

Abstract: The goals of this study were to quantify organic matter source utilization by consumers in the freshwaterdominated region (East Bay) of a high river flow estuary and compare the results to consumers in marine-influenced sites of the same estuary to understand how organic matter utilization by consumers may be changing along the salinity gradient. We used the results from these evaluations to establish the baseline against which we isotopically determined trophic level for consumers in East Bay. Average isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Consumer δ has been observed from river to ocean in estuaries as well (Middelburg and Nieuwenhuize, 1998;Wilson et al, 2009Wilson et al, , 2010. More depleted δ 15 N isotopic composition of consumers in the nearshore of Lake Michigan relative to upstream sites is consistent with previous observations of Lake Michigan incorporating atmospheric N into the food web (MacGregor et al, 2001).…”
Section: Sitesupporting
confidence: 86%
“…Consumer δ has been observed from river to ocean in estuaries as well (Middelburg and Nieuwenhuize, 1998;Wilson et al, 2009Wilson et al, , 2010. More depleted δ 15 N isotopic composition of consumers in the nearshore of Lake Michigan relative to upstream sites is consistent with previous observations of Lake Michigan incorporating atmospheric N into the food web (MacGregor et al, 2001).…”
Section: Sitesupporting
confidence: 86%
“…In river‐dominated estuaries, fluvial input is an important source of detritus (Lin et al , 2007; Wilson et al , 2010). In some estuaries, particularly those that are deprived of an adequate river flow, detritus is mainly autochthonous and is usually derived from intertidal and subtidal plants; in the warm‐temperate Kromme Estuary, for example, Heymans & Baird (1995) determined that marsh halophytes were responsible for 78% of primary production, of which 90% was first broken down to detritus before entering the food web.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of copepods and oysters suggests that ingestion of microzooplankton is less important for oysters and/or that oysters may be assimilating some depleted organic matter from the surface sediments or terrestrial particulate organic matter (POM). Wilson et al (2010) have suggested that benthic microalgae growing on the sediment surface may also be a significant food source to bay consumers.…”
Section: Discussion δ 15 N In Macroalgae and Oystersmentioning
confidence: 99%
“…The low δ 15 N values coupled with the understanding that benthic resuspension of surficial materials is likely common in this shallow, wind mixed system suggest that sediment POM contributes to oyster diets. In fact, Wilson et al (2010) estimated that benthic organic matter comprised about 20% of oyster diets. Chanton and Lewis (2002) also used δ 13 C values in a simple two endmember mixing model to estimate that about 40% of the organic matter in the sediments was of terrestrial origin.…”
Section: Discussion δ 15 N In Macroalgae and Oystersmentioning
confidence: 99%
See 1 more Smart Citation